Repeated photoporation with graphene quantum dots enables homogeneous labeling of live cells with extrinsic markers for fluorescence microscopy - Liu, Jing; Xiong, Ranhua; Brans, Toon; Lippens, Saskia; Parthoens, Eef; Zanacchi, Francesca Cella; Magrassi, Raffaella; Singh, Santosh K.; Kurungot, Sreekumar; Szunerits, Sabine; Bove, Hannelore; Ameloot, Marcel; et al. (Light-Science & Applications, 2018)
In the replacement of genetic probes, there is increasing interest in labeling living cells with high-quality extrinsic labels, which avoid over-expression artifacts and are available in a wide spectral range. This calls for a broadly applicable technology that can deliver such labels unambiguously to the cytosol of living cells. Here, we demonstrate that nanoparticle-sensitized photoporation can be used to this end as an emerging intracellular delivery technique. We replace the traditionally used gold nanoparticles with graphene nanoparticles as photothermal sensitizers to permeabilize the cell membrane upon laser irradiation. We demonstrate that the enhanced thermal stability of graphene quantum dots allows the formation of multiple vapor nanobubbles upon irradiation with short laser pulses, allowing the delivery of a variety of extrinsic cell labels efficiently and homogeneously into live cells. We demonstrate high-quality time-lapse imaging with confocal, total internal reflection fluorescence (TIRF), and Airyscan super-resolution microscopy. As the entire procedure is readily compatible with fluorescence (super resolution) microscopy, photoporation with graphene quantum dots has the potential to become the long-awaited generic platform for controlled intracellular delivery of fluorescent labels for live-cell imaging.